Simple indirect forecast of remaining discharge energy of lithium-ion battery under future complex discharge conditions. (July 2022) - Liu, Changhe; Hu, Minghui; Jin, Guoqing; Fu, Chunyun; Yang, Huiqian; Jia, Qinglong
Abstract: The remaining discharge energy (RDE) of the battery is influenced by future working conditions, so its forecast method should be given priority to simplicity and rapidity, and second to accuracy. In the present study, RDE can be forecasted with an indirect method, based on segment average of the future discharge current sequence, by using the remaining chemical energy and heat loss. With the battery reversible heat taken into account, this method avoids time-consuming calculation of the future terminal voltage sequence and realizes closed-loop forecast relying on feedback of cumulative discharge capacity. Besides, the cut-off cumulative discharge capacity, as an important basis for RDE forecast, can be obtained by a joint method of Peukert equation and terminal voltage calculation with a small amount of calculation. According to experiments, the maximum root mean square error (RMSE) of 3 cells' RDE forecast by using the proposed method under 6 discharge conditions remains within 300 mWh with the calculation time greatly reduced. Even for another kind of battery with small capacity, the maximum error can be guaranteed within 100 mWh, which proves that this method has good generalization ability. Highlights: Transfer the target from SOE to RDE A joint method is proposed for cut-off cumulative discharge capacity calculation. An indirect method is proposed to forecast the remaining discharge energy. The indirect method is more simple and efficient.